PENGGUNAAN PORTAL COVID19.GO.ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI COVID 19 DI LINGKUNGAN STARBUCKS COFFEE KAWASAN TANGERANG - Nurianna, Anis; suraya, suraya (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
This Research aim to examine there is an effect of using the covid19.go.id portal to seeking information about covid 19 in the Starbucks Coffee Tangerang by using the Uses Gratification theory - Gratification Sought and Gratification Obtained. The research was conducted with survey method and use a positivist paradigm with a quantitative approach, with Inferensial statistical analysis using simple linear regression. The data collection used a questionnaire distributed to 100 respondents in the Starbucks Coffee Tangerang. The results shown that there is a positive influence on seeking information needs of covid 19. It is also found that the integrity dimension is an important dimension in the variable of using the covid19.go.id portal where it is assumed that the community has a knowledge motive about covid 19 for the benefit of socializing and helping carry out their social roles in society. the variable of seeking information needs, the affective dimension becomes a dimension that has a big influence, where people in Starbucks Coffee Tangerang use the covid19.go.id portal to get attention and appreciation from the environment, family, and people around, in other words, become people who are always up-to-date in information about covid 19 in Indonesia.